EVALUATION OF RATIONALITY OF EXPENSES ON TREATMENT OF SEVERE COMMUNITY-ACQUIRES PNEUMONIA IN MULTI-PROFILE HOSPITAL - I. V. Demko; N. V. Gordeeva; E. N. Bochanova; N. I. Golovina; A. Yu. Kraposhina; I. A. Soloveva; E. A. Sobko; T. V. Gaygolnik; S. V. Chubarova (IRBIS LLC, 2016)
Purpose - to study rationality of financial expenses on the treatment of patients with the severe pneumonia.Materials and methods. It was selected 30 medical histories of patients with severe community-acquires pneumonia passing hospitalization in pulmonology department and department of intensive care in 2004, 2011 and 2014. The frequency analysis was applied to studying the structure of the carried-out drug treatment and identification of frequency of the separate medicinal preparations. We have data about the cost of drug which were received from the database of «1C: Drugstore» of regional clinical hospital.Results. Expenses on the treatment of severe community-acquires pneumonia according to 2014 year are rational, 92.23% of expenses are vitally necessary drug entering into modern clinical references. According to the ABC/VEN analysis during the period from 2004 till 2014 we found positive dynamics of increase of expenditure of money at category V. The appreciable attention should be paid to the treatment of accompanying pathology in the therapy of severe communityacquires pneumonia which can make heavier a current of basic disease and become the reason of complications, often fatal. Costs of the medicinal preparations for treatment of the accompanying pathology in 2014 year was made 6.27% that it is necessary to consider at advance planning of provision of medicines in pulmonology department.Conclusion. The results received by us testify about rational use of financial costs on treatment of patients with severe community-acquires pneumonia.